2011
DOI: 10.1177/1461445610387736
|View full text |Cite
|
Sign up to set email alerts
|

THERAPY IS A JOURNEY as a discourse metaphor

Abstract: Although much has been written about the use of metaphors during psychotherapy sessions, the complementary question of how the therapeutic process might itself be metaphorically conceptualized is seldom asked. This article adopts the notion of ‘discourse metaphors’ (Zinken et al., 2008) and provides a case study of the metaphor THERAPY IS A JOURNEY across various levels of psychotherapeutic discourse, including the formulation of theoretical constructs, pedagogical frameworks and transcripts of actual therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 27 publications
0
14
0
2
Order By: Relevance
“…I share with McMullen the desire to see metaphors more fruitfully used in counseling, but I have suggested that another route to this outcome lies in a keener appreciation, on counselors’ part, of parallel developments in different aspects of metaphor theory. These other aspects include, but are not limited to, the nature of conceptual materials that constitute metaphoric sources (Kövecses, 2010), the variation of conceptual metaphors across different speakers (Kövecses, 2005; Tay, 2011), and nonlinguistic modalities of metaphor (e.g., audio, visuals; Forceville, 2006), all of which have implications for the applied field of counseling waiting to be uncovered.…”
Section: Resultsmentioning
confidence: 99%
“…I share with McMullen the desire to see metaphors more fruitfully used in counseling, but I have suggested that another route to this outcome lies in a keener appreciation, on counselors’ part, of parallel developments in different aspects of metaphor theory. These other aspects include, but are not limited to, the nature of conceptual materials that constitute metaphoric sources (Kövecses, 2010), the variation of conceptual metaphors across different speakers (Kövecses, 2005; Tay, 2011), and nonlinguistic modalities of metaphor (e.g., audio, visuals; Forceville, 2006), all of which have implications for the applied field of counseling waiting to be uncovered.…”
Section: Resultsmentioning
confidence: 99%
“…This analysis suggests that there are few conventionally available linguistic resources available to carers to supply non-medical accounts of recovery (Tay, 2011), and such accounts are hedged with uncertainty. This reflects a wider concern arising from recovery movement, that recovery is so deeply personal that it defies definition (Barker & Buchanan-Barker, 2010).…”
Section: Extractmentioning
confidence: 99%
“…El intercambio conversacional se basó en la introducción de la metáfora del tratamiento como viaje, a través de preguntas acerca del inicio como partida, el proceso como trayecto y la reinserción al medio de procedencia como próximo arribo. La metáfora del viaje tiene un arraigado sustrato cultural (Lakoff & Johnson, 1995;Mikkonen, 2007;Smelser, 2009) y ha sido aplicada al proceso de tratamiento en general y en el abordaje del consumo de drogas en particular (Epston & White, 1992;Hegarty, Smith, & Hammersley, 2010;Shinebourne & Smith, 2010;Tay, 2011). Al término de las sesiones se elaboró una carta que reconstruía aspectos significativos del proceso recuperando la voz de los consultantes (White, 2002(White, , 2007White & Epston, 1993), la cual les fue entregada como elemento de cierre.…”
Section: Descripción De La Intervenciónunclassified